Response of Some Trace Elements to Soccer Match Performed Different Times of Day in Young Sedentary Male: Exercise Time and Trace Elements - Algul, Sermin; Baltaci, Saltuk Bugra; Bengu, Aydın Sukru; OguzOzcelik, (Progress in Nutrition, 2022)
OBJECTIVE: We aimed to examine effects of soccer match induced metabolic stress on levels of some trace elements.MATERIALS and METHODS: Fourteen sedentary male subjects randomly performed three indoor soccer matches (2 x 30 minute) in morning, afternoon and at night on different days. Venous blood samples were taken before and after match. Plasma malondialdehyde levels measured by High Performance Liquid Chromatography. Total antioxidant capacity and total oxidant capacity were estimated using a commercially available enzyme-linked immunosorbent assay kit. Plasma iron, copper and zinc levels was measured using an Atomic Absorption Spectrophotometer.RESULTS: Significant increases were found in iron, malondialdehyde and total oxidant capacity in all matches (p